Screening for Hepatitis C Among Community Health Center Patients by Ethnicity and Language Preference - Brian L. Chan, MD, MPH; David Ezekiel-Herrera, MS; Steffani R. Bailey, PhD; Miguel Marino, PhD; Jennifer A. Lucas, PhD, MPH; Sophia Giebultowicz, MS; Erika Cottrell, PhD, MPP; Joe Carroll, MD; John Heintzman, MD, MPH (Elsevier, 2023)
Introduction: Hepatitis C virus is associated with high morbidity and mortality-chronic liver disease is a leading cause of death among Latinos in the U.S. Screening for hepatitis C virus in community health center settings, which serve a disproportionate percentage of Latinos, is essential to eradicating hepatitis C virus infection. We assessed hepatitis C virus screening disparities in adults served by community health centers by ethnicity and language preference. Methods: This was an observational cohort study (spanning 2013-2017) of adults born in 1945-1965 in the Accelerating Data Value Across a National Community Health Center Network electronic health record data set. Our exposure of interest was race/ethnicity and language preference (non-Hispanic White, Latino English preferred, Latino Spanish preferred). Our primary outcome was the relative hazard of hepatitis C virus screening, estimated using multivariate Cox proportional hazards regression. Results: A total of 182,002 patients met the study criteria and included 60% non-Hispanic Whites, 29% Latino Spanish preferred, and 11% Latino English preferred. In total, 9% received hepatitis C virus screening, and 2.4% were diagnosed with hepatitis C virus. Latino English-preferred patients had lower rates of screening than both non-Hispanic Whites and Latino Spanish preferred (5.5% vs 9.4% vs 9.6%, respectively). Latino English preferred had lower hazards of hepatitis C virus screening than non-Hispanic Whites (adjusted hazard ratio=0.56, 95% CI=0.44, 0.72), and Latino Spanish preferred had similar hazards of hepatitis C virus screening (adjusted hazard ratio=1.11, 95% CI=0.88, 1.41). Conclusions: We found that in a large community health center network, adult Latinos who preferred English had lower hazards of hepatitis C virus screening than non-Hispanic Whites, whereas Latinos who preferred Spanish had hazards of screening similar to those of non-Hispanic Whites. The overall prevalence of hepatitis C virus screening was low. Further work on the role of language preference in hepatitis C virus screening is needed to better equip primary care providers to provide this recommended preventive service in culturally relevant ways.